2016
DOI: 10.1021/acs.est.5b04287
|View full text |Cite
|
Sign up to set email alerts
|

Formation of PCDD/Fs in Oxidation of 2-Chlorophenol on Neat Silica Surface

Abstract: This contribution studies partial oxidation of 2-chlorophenol on surfaces of neat silica at temperatures of 250, 350, and 400 °C; i.e., temperatures that frequently lead to catalytic formation of polychlorinated dibenzo-p-dioxins and polychlorinated dibenzofurans (PCDD/Fs) from their precursors. We have identified 2,6-dichlorophenol (2,6-DCPh), 2,4-dichlorophenol (2,4-DCPh), and 2,4,6-trichlorophenol (2,4,6-TriCPh), but have detected no chlorinated benzenes (CBzs). The detected chlorinated and nonchlorinated D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 35 publications
0
34
0
Order By: Relevance
“…In Table 4, we assemble literature reported activation barriers for the fission of phenolic O-H bond over metallic and metal oxide surfaces (Altarawneh et al, 2009b;Honkela et al, 2012;Li et al, 2015;Assaf et al, 2016;Mosallanejad et al, 2016;Pan et al, 2019). It is evident that the clean Fe and Cu surfaces and their partially oxidized configuration require higher activation energies to transform phenol into a surface-bound phenolate.…”
Section: The Effect Of the Oxygen: Cu(100)_o 1 And Fe (100)_o 1 Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…In Table 4, we assemble literature reported activation barriers for the fission of phenolic O-H bond over metallic and metal oxide surfaces (Altarawneh et al, 2009b;Honkela et al, 2012;Li et al, 2015;Assaf et al, 2016;Mosallanejad et al, 2016;Pan et al, 2019). It is evident that the clean Fe and Cu surfaces and their partially oxidized configuration require higher activation energies to transform phenol into a surface-bound phenolate.…”
Section: The Effect Of the Oxygen: Cu(100)_o 1 And Fe (100)_o 1 Surfacesmentioning
confidence: 99%
“…Seemingly unreacted silica surfaces also facilitate rupture of the phenolic's O-H bond (Mosallanejad et al, 2016). In our recent theoretical studies (Assaf et al, 2016), we illustrated thermo-kinetics parameters for the dissociative adsorption of phenol yielding adsorbed phenolate species over surfaces of dehydroxylated alumina and OH-alumina clusters.…”
Section: Introductionmentioning
confidence: 95%
“…Radical species formed from thermal degradation events have generally been referred to as environmentally persistent free radicals ( EPFRs ) and represent a class of reactive species that have prolonged life time even under ambient environmental conditions [41]. These radicals may be precursors for a group of environmentally persistent volatile organic pollutants such as phenols, dioxins and benzofurans which can easily be converted to the most toxic environmental pollutants ever known-polychlorinated dioxins and polychlorinated dibenzo furans ( PCDD∕Fs ) in presence of small amounts of chlorine and a transition metals such as iron or copper and/or their corresponding oxides [41,42].…”
Section: Elemental Composition Of Char and Electron Paramagnetic Spectramentioning
confidence: 99%
“…Dioxins are formed from halogenated phenols via two general mechanisms: homogeneous gas-phase mechanism and heterogeneous metal mediated mechanism. Although over 70% of all dioxins are formed through surface-mediated reactions over catalytic surfaces in the post-ame, cool zone of combustion systems at the temperature range of 200À600 C, [33][34][35][36][37] the homogeneous gas-phase mechanism also make a signicant contribution to the dioxin formations at high temperatures (>600 C). 38,39 Studies have shown that the radical-radical coupling of halogenated phenoxy radicals plays a considerable role in the homogeneous gas-phase formation of dioxins and furans.…”
Section: Introductionmentioning
confidence: 99%